Teaching Descriptive Text Writing Through Indonesian Traditional Cartoons: An Ethno-Pedagogical and Constructivist Approach - Nugroho, Eko; Inawati, Iin; Tino, Marilio D. (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2024)
Writing descriptive texts is a fundamental skill in English as a Foreign Language (EFL) education, yet it often presents challenges for students due to its reliance on creativity, vocabulary, and structural coherence. Traditional Indonesian cartoons, rooted in local culture and values, offer a unique ethno-pedagogical approach that aligns with constructivist principles by promoting active, student-centered learning. This study investigates how traditional Indonesian cartoons can be used as an effective tool to teach descriptive text writing, exploring their impact on student engagement, cultural awareness, and writing proficiency. This qualitative case study was used in this study. Data were collected through questionnaires, interviews, and classroom observations. The findings revealed that the teacher effectively integrated traditional Indonesian cartoons to enhance classroom interactions and align teaching with local cultural contexts. The teacher reported that using these cartoons created a positive and engaging learning environment, motivating students and stimulating their intellectual curiosity. Students expressed high levels of enjoyment during the learning process, with 80% indicating a strong preference for learning to write descriptive texts using traditional cartoons. Furthermore, the incorporation of culturally familiar materials facilitated deeper connections between students and the learning content. The study concludes that traditional Indonesian cartoons serve as a valuable ethno-pedagogical resource, promoting cultural awareness and supporting constructivist learning by actively engaging students in meaningful and enjoyable writing activities.